Multilevel Analysis Association of Soil Transmitted Helminths and Stunting in Children Aged 6-12 Years Old in Pinrang District, South Sulawesi - Putri Andini Muslimah; Harsono Salimo; Yulia Lanti Retno Dewi (Masters Program in Public Health, 2020)
Background: Stunting in children is often associated with infectious diseases, one of which is Soil Transmitted Helminths (STH). Worms in child